Necessidades assitenciais e educativas de cuidadores de crianças dependentes de tecnologia - Lima, Muriel Fernanda de (2013)
The technical and scientific advances in health care allowed significant improvement of indices and survival of children with cases previously sentenced to death. Along with these advances a new demand for health care assistance, the children with chronic diseases that need technological devices to maintenance of a vital activity, these also named Technology-dependent Children (TDC). However, children with chronic condition have fragilities and limitations, requiring a new perspective regarding to care. In this sense, the family needs to reorganize and adapt for the redistribution of roles and rank a member to take care integrally of the child. This post, the objective of this research was analyzing the process of domiciliary care by family caregiver of Technology-dependent Children. It is a descriptive research with qualitative approach that utilized the Content Analysis as methodological reference, thematic anchored in the theoretical framework of Symbolic Interactionism. 14 family TDC preferred caregivers participated of the study, and they were accompanied in the hospital and in the domicile after the child´s hospital discharged. The data were collected between March and June of 2013, by means of interviews with the support of a semi-structured guide and non-participant observation with the aid of an observation guide. The data collection took place in two moments, initially in Pediatric Intensive Care (PIC) of University Hospital of Maringá - Paraná, for catchment, observation and interview of the research subjects; and after in domicile, after the TDC´s discharge, with view to verifying complex care and the demands brought about by this reality. The possibility of the permanence of the caregiver and learning complex care during hospitalization were considered insufficient to guarantee security and family empowerment. The difficulties reported by the caregivers during this period referred mainly to the need of doubts clarification regarding to the diagnosis, handling and technology to be used by the TDC, organization and family dynamic to the child care. Among the care, the caregivers had some obstacles to be initially overcome concerning to fear, worry, support, responsibility and home´s financial maintenance. Faced with this, it emphasizes the need of the public organizations and health service´s attention to the development of actions that contemplate the necessities of knowledge and care of the family caregivers since the diagnosis period until the transpose of complex care in the domicile. The meanings built highlight the need for expanding the network of family care, including committed articulated services to the continuity and quality of care. The study also highlighted gaps that refers to qualification of the professionals working with families, they also see the assistance need of a family member with chronic disease, not the family center as a unit that needs to be treated to the effectiveness of health educational actions.